The Role of Physical Activity and Mortality in Hemodialysis Patients: A Review - Fan Zhang; Hui Wang; Weiqiong Wang; Huachun Zhang (Frontiers Media S.A., 2022)
Available data indicated that physical activity was related to improved outcomes in hemodialysis patients. Multiple observational studies involving different cohorts have reported that increased physical activity level was associated with decreased mortality among hemodialysis patients. Therefore, promoting physical activity has become an increasingly critical and promising approach to improving cardiovascular health and clinical outcomes in hemodialysis patients. This review summarizes the published articles regarding physical activity and hemodialysis patients, focusing on mortality and strategy to promote physical activity.